Notes on Oceanic Pharmacology - Nicholas Anderman (Media Theory)
Recent oceanographic research indicates that the Atlantic Meridional Overturning Circulation (AMOC), one of the earth’s major oceanic circulatory systems, has begun to weaken rapidly. Should the system continue to slow, it will have potentially devastating consequences for climatic negentropy. Given this situation, the world ocean might be understood as a vast, watery pharmakon: a material space of ambivalent effects, yielding up both life and death on a planetary scale. This article explores the pharmacological dimensions of seawater, in four parts. Part one establishes the concept of oceanic pharmacology in conversation with Jacques Derrida’s reading of Plato’s Phaedrus. Part two looks at Bernard Stiegler’s theorization of Derridean diffe?rance and phusis, or nature, in order to argue that the ocean is not a natural thing at all, but must instead be understood as a technical object, i.e. as pharmakon. Part three critically surveys geophysical research on AMOC decline in an effort to shift the concept of oceanic pharmacology into a materialist register. Finally, part four takes up the crucial temporal dimensions of oceanic pharmacology in the context of Christina Sharpe’s notion of residence time. Thinking with Sharpe, the paper concludes with a discussion of what I call resonance time: an oceanic temporality of pharmacological uncertainty.